Magnum Opus : the Cycle Plays of Eugene O'Neill - Brietzke, Zander, 1960- (Yale University Press, 2021)
From 1935 to 1939, Eugene O'Neill worked on a series of plays that would trace the history of an American family through several generations. He completed just two of the proposed eleven plays-A Touch of the Poet and More Stately Mansions-which Zander Brietzke argues represent the core of the entire cycle. Combining archival research, literary analysis, and theatrical imagination, Magnum Opus invites an audience to see this unusual and exciting epic as a historical drama of our time.